Diagnostic Description of Ischemic Stroke Patients with Type 2 Diabetes Mellitus in Royal Prima Medan General Hospital - Halim, Michael (JURNAL KEDOKTERAN RAFLESIA, 2021)
AbstractStroke is a focal cerebral dysfunction that occurs for 24 hours or more, which can cause disability or death due to spontaneous bleeding or inadequate blood supply. The stroke itself can be divided into ischemic and hemorrhagic. Ischemic stroke is a sudden loss of blood circulation in the brain area. Diabetes mellitus is a metabolic disease characterized by hyperglycemia that occurs due to abnormalities in insulin, insulin action, or both. Diabetes mellitus is divided into type 1, type 2, and gestational. Type 2 diabetes mellitus is a metabolic disorder usually characterized by increased blood sugar due to a decrease in insulin by pancreatic beta cells and insulin resistance. The purpose of this study was to determine the diagnostic picture of ischemic stroke patients with type 2 diabetes mellitus and to determine the distribution of proportions based on sociodemographic characters, procedures for diagnosis, management, and complications of the disease. This research is descriptive, retrospective with a case study design and a sample of 30 medical records at Royal Prima Hospital, which will then be analyzed using the SPSS application. The results showed the distribution of the proportion of ischemic stroke patients with T2DM in the elderly, male gender, blood sugar levels 200-300 mg/d, cholesterol above 200, and previous disease history. Based on the research results that have been done, it is concluded that people who have had an ischemic stroke almost always have a history of diabetes mellitus, both type 2 and vice versa, and have congenital supporting diseases such as hypertension. Keywords: Stroke, ischemic stroke, type 2 diabetes mellitus  AbstrakStroke merupakan disfungsi serebral fokal yang terjadi selama 24 jam, bahkan lebih. Sehingga dapat menyebabkan disabilitas atau kematian karena terjadi pendarahan spontan atau pasokan darah yang tidak memenuhi. Stroke sendiri dapat dibagi menjadi iskemik dan hemoragik. Stroke iskemik merupakan hilangnya sirkulasi darah didaerah otak secara tiba-tiba. Diabetes mellitus merupakan penyakit metabolik dengan karakteristik hiperglikemia yang terjadi karena kelainan insulin, kerja insulin atau keduanya. Diabetes mellitus dibagi menjadi DM tipe 1, DM tipe 2, gestasional. Pengertian dari diabetes mellitus tipe 2, yaitu merupakan gangguan metabolik yang biasanya ditandai dengan kenaikkan gula darah akibat penurunan insulin oleh sel beta pankreas dan resistensi insulin. Tujuan penelitian ini adalah untuk mengetahui gambaran diagnostik pasien stroke iskemik terhadap diabetes mellitus tipe 2, serta untuk mengetahui distubusi proporsi berdasarkan karakter sosiodemografis, tata cara diagnosis, penatalaksanaan dan komplikasi penyakit. Penelitian ini bersifat deskriptif, retrospektif dengan desain studi kasus dan jumlah sampel sebanyak 30 data rekam medis di RSU Royal Prima yang selanjutnya akan dianalisa menggunakan aplikasi SPSS. Hasil penelitian didapatkan distribusi proporsi pasien stroke iskemik dengan DMT2 pada usia lansia, jenis kelamin laki-laki, kadar gula darah 200-300mg/d, kolestrol diatas 200 dan memiliki riwayat penyakit sebelumnya. Berdasarkan hasil penelitian, dapat disimpulkan hasil: orang yang pernah terkena stroke iskemik hampir selalu memiliki riwayat penyakit diabetes mellitus baik tipe 2 dan sebaliknya, serta memiliki penyakit bawaan pendukung seperti hipertensi.                                                                                          Kata kunci: Stroke, stroke iskemik, diabetes mellitus tipe 2